General Characteristics of Contracts with a Foreign Element - Shubina, Olga (Research Papers, 2018)
In the theses we analyze some legal rules provisions сconclusion of a contract with a foreign element. The author examines the general characteristics of contracts with a foreign element and makes suggestions on the procedure for concluding agreements.